Interpersonal approach to the ability to check pregnancy with peb pregnant women in Kedunglangkap Hamlet - Yuliani, Ika; Setyowati, Lisus; Ernawati, Iit (International Journal of Nursing and Midwifery Research, 2023)
Ante Natal Care (ANC) is the administration of health checks provided to mothers during their pregnancies according to antenatal check guidelines.  The aim of this research was to and the impact of interpersonal approach to agreement of antenatal care on expectants with eclampsia in Kedunglankap. This research used pre experimental design with pre-post test one group design. The sample were 34 expectants by total sampling and used Wilcoxon test to find the result . The results research the respondents who agreed to get antenatal care were 19 respondents (55.9%). Then who didn’t agree were is 15 respondents (44.1%), who greed to get antenatal care increasing to 29 respondents (85.3%). And didn’t agreed being 5 respondents (14.7%). Wilcoxon test o this research got the result if p value <0,005(p=0,002), which undicatedif there was an effectiveness of  personal app to antenatal care agreement of expectants with eclampsia in Kedunglangkap. Great expectations if midwives will always upgrade the knowledge and skill on giving antenatal and increasing interpersonal app on communication to patients.